PENINGKATAN KAPASITAS PENGELOLA USAHA PEMBUATAN MERCHANDISE PIN MELALUI PELATIHAN COREL DRAW DI UNIT USAHA YAYASAN FASTABIQUL KHAIRAT - Eka Ardhianto; Endang Lestariningsih; Widiyanto Tri Handoko; Hari Murti; Edy Supriyanto (Join, 2022)
Business development can be done in many ways, one of which is to increase product variations. This method was achieved by the business unit of the Fastabiqul Khairat Foundation by developing a printing business in the form of making marchandise pins. The limited ability and knowledge of business managers becomes an obstacle for the business development plan. Based on these problems, this Community Service activity aims to provide training with pin graphic design material using the corel draw application device. This activity is carried out in several stages, namely the planning, training, and mentoring stages. As an evaluation indicator, pretest and posttest questionnaires were filled out. The results obtained are that the corel draw graphic design training activities have a significant impact on the knowledge and understanding of participants in making machine pin designs